Feminist Language And Women’s Image In Balinese POP Song Entitled Wek Igis - Julyandini, Luh Nurcahya; Sariyani, Ni Nyoman; Arlinayanti, Kadek Dwi (Jayapangus Press, 2023)
Balinese pop song has a simple characteristic and is easily remembered by the public because this song characterizes the expression of the author’s feelings, which are written into the content and the life phenomenon. Balinese pop song is highly favored among the Balinese people because it has its own characteristic of using the Balinese language and is easy to learn because it has simple lyrics. It has been proven that in Bali, many singers sing Balinese pop songs such as Widi Widiana, Panji Kuning, Yong Sagita, Dek Ulik, A.A. Raka Sidan, Putri Bulan, and Dek Arya. One of the most famous Balinese pop songs is Wek Igis. This song tells about how women are from the man's point of view and also contains love. Furthermore, this love song also expresses joy, sadness, and anger. There are two singers in this album entitled Wek Igis, namely Dek Arya, and Putri Bulan. This song is one of the songs that represent the feminist aspect or the image of women. The image of women is a form of mental-spiritual image and daily behavior expressed by women in various aspects, namely physical and psychological aspects as a woman’s self-image and family and community aspects as a social image. By the existence of the feminist language presented in the lyrics of the Balinese pop song entitled Wek Igis, it aims to preserve and develop modern Balinese literature, especially in Balinese pop songs, and to raise the degree of women’s image in society’s point of view. In this study, two theories were used in the manuscript: structural theory according to I.A. Richard (in Tarigan, 2004) and feminist psychoanalysis theory according to Marxists and Socialists (in Rosemarie, 2010). The research method was qualitative, while the supporting instruments were transcription, interviews, literature, and documentation. The data analysis used in this research was descriptive data analysis technique and qualitative data analysis technique. The results of this study discussed the structure of the lyrics in the song entitled Wek Igis. The lyrical structure of the song is divided into two, namely, method and essence. The data studied only focuses on diction (word choice), imagery, and rhyme, and the essence studied was only on the song’s message. The image of women is perceived from feminist psychoanalysis aspects, such as caring women and loyalty expressed through the song’s message. The feminist language in this song is also found in Hindu literature, specifically in the Manava Dharmasastra.